Pemanfaatan Limbah Plastik Polyprophylene (PP) dan Sekam Padi Menjadi Papan Partikel - Meldayanoor Meldayanoor; Arifin arifin; Rusuminto Syahyuniar (Jurnal Teknologi Agro-Industri, 2017)
ABSTRACT The need for board materials continues to increase, therefore the need for new innovations in the form of utilization of plastic waste and rice husks are used as raw material for making particle board where the waste plastic as adhesive and rice husk as filler. The purpose of this research is to know the physical properties such as density, moisture content, and water absorption in order to determine the exact formulation on the particle board that meets the quality standard. SNI 03-2015-2016 quality standard is used as a reference comparison of the results of testing stages of research starting from the processing of raw materials plastick and chaff into sebuk, mixing, and formation of particle board until the testing phase. Elements of particle board formation are rice husks and polyprophylene plastics as adhesives made with Plastic compositions: 40%: 60% 50%: 50% and 40%: 40%: husks. In testing the physical properties of the results showed that the right composition is 60%: 40% because it has results with a particle density of 0.83 g /cm3, a water content of 4.87%, and a water absorption of 10.67%. It is the best result of some predefined compositions and meets the quality standard of SNI 03-2015-2016 Keywords: From The board particles, polyprophylene plastic, chaff rice